EVALUASI KEKUATAN KOLEKSI DI PERPUSTAKAAN UNIVERSITAS ISLAM NEGERI SUNAN KALIJAGA YOGYAKARTA - Djazim Rohmadi; Tafrikhuddin Tafrikhuddin (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
In terms of information and collection dissemination in order to realize the service for users, tailor service-a service to work on a patchwork of any lack of information necessity by library users-can be used to fulfill the need. In reality, no matter how big or how many amount of collection a library, it is still unable to fulfill the need of their users for their necessity diversity of information. Hence, mutual sharing and cooperation in a library network will help and complete each other for any lack of information or collection in one of library within the network. The collection capacity will be able to support the success of University Tri Dharma especially in order to elevate each study program of every faculty or in every department of the university. The library last paradigm is service, whether the library has successfully providing the necessity service or not is uncertain if the pressure point and its collection capacity are veiled. Therefore, it is important to plot and evaluate collection capacity for the sharing purpose. This knowledge of the library collection capacity will also help to prepare for further cooperation with another library which has collection capacity too. However, the question is whether the library of Sunan Kalijaga Islamic State University has known its collection capacity? Thus, this is the importance of this research.Keywords: collection capacity, information, library